2021
DOI: 10.1002/art.41621
|View full text |Cite
|
Sign up to set email alerts
|

Association of Higher Hydroxychloroquine Blood Levels With Reduced Thrombosis Risk in Systemic Lupus Erythematosus

Abstract: Objective. Hydroxychloroquine (HCQ) has a primary role in the prophylaxis and treatment of systemic lupus erythematosus (SLE) and may be protective against thrombosis in SLE. Optimal weight-based dosing of HCQ is unknown. This study was undertaken to examine the usefulness of HCQ blood monitoring in predicting thrombosis risk in a longitudinal SLE cohort.Methods. HCQ levels were serially quantified from EDTA whole blood by liquid chromatography-tandem mass spectrometry. The mean HCQ blood levels calculated pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…The effectiveness of hydroxychloroquine in systemic disease and\or antiphospholipid syndrome has been assessed also regarding the reduction of thrombotic rate. Particularly the reduction was associated to the increase of the dosage of hydroxychloroquine [ 14 , 15 ]. Indeed, the rate of venous thromboembolism in our cohort did not differ between the group that performed pre-exposure with hy-droxychloroquine and the group not receiving HC during the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of hydroxychloroquine in systemic disease and\or antiphospholipid syndrome has been assessed also regarding the reduction of thrombotic rate. Particularly the reduction was associated to the increase of the dosage of hydroxychloroquine [ 14 , 15 ]. Indeed, the rate of venous thromboembolism in our cohort did not differ between the group that performed pre-exposure with hy-droxychloroquine and the group not receiving HC during the disease.…”
Section: Discussionmentioning
confidence: 99%
“… 18 This remains to be documented and there are some trials that are trying to support it. 19 21 Furthermore, high HCQ blood levels are associated with reduced thrombotic events in SLE patients, 22 which is also a clinical manifestation of SARS-CoV-2 patients. On the other hand, a study by Koning et al found no protection for SARS-CoV-2 infection or the development of the severe form of the disease with the use of HCQ in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, HCQ therapy has been associated with positive effect on traditional CV risk factors and a reduction of CV morbidity and mortality in SLE 18 19. Moreover, maintaining an average HCQ whole blood level >1.068 ng/mL significantly reduced the risk of thrombosis in SLE, based on data from 739 patients of the John Hopkins cohort 28. However, it was still unclear if the protective CV effect of HCQ is an indirect result of better control of disease activity or a direct effect of HCQ on the endothelium.…”
Section: Discussionmentioning
confidence: 99%